Convenient and Improved One Pot Synthesis of Imidazole - PRASANTHI, V.; SIVANADH, M.; NAGESWARA RAO, KARUSALA; V. BASAVESWARA RAO, MANDAVA (Asian Journal of Chemistry, 2010)
An improved and convenient one pot synthesis of 99 % pure imidazole using (40.0 w/w) glyoxal (1 mol), 25 % aquous ammonia (4 mol) and 35 % formaldehyde (w/w) (1.125 mol) under the temperature conditions of 70-90°C. Various combinations of ammonia, glyoxal and formaldehyde are studied. When the reactions was carried out using ammonia four times of that of glyoxal and formaldehyde 1.125 times to that of glyoxal, it was observed that the better yields of imidazole are obtained with high purity.